KEADILAN SOSIAL DALAM KEUANGAN SYARIAH - M. Roem Syibly (Millah: Journal of Religious Studies, 2015)
Social justice in the Islamic economy is based on spiritual commitment and the concept of universal brotherhood among human beings which requires that all resources be sacred trust God, used to realize Maqashid Shari’ah, it is the fulfillment of human life. This paper describes the theory of social justice that focus on Islamic financial. The foundation of Islamic justice can be seen from al-Qur’an Surah al-Hadid: 25 affirming that justice has been emphasized by the Qur’an as the primary mission of the Prophets sent by God Almighty, including economic justice and the elimination of the income gap. Social justice in Islam is the implication of the fundamental principle underlying all the teachings of Islam, namely monotheism. At the level of practice, Islam prohibits usury, Islam seeks to build a society based on honesty and fairness. Justice in this context has two dimensions, namely the financiers are entitled to a reward, but should be commensurate with the risk and effort required, and the reward is determined by the profit. Implementation of Islamic justice theory in Islamic finance can be seen from mudharabah and Musharaka or commonly known as a profit and loss sharing.